EFFECT OF SYSTEMIC FUNGICIDE BENLATE (BENOMYL) ON SEEDLING GERMINATION AND GROWTH IN ALLIUM CEPA L. - P.V. PULATE (International Journal of Pharma and Bio Sciences, 2016)
The seeds of Allium cepa L.Var.N-53 were selected and used for following research. The healthy, untreated and uniform seeds were treated with different concentration of benlate (0.02%, 0.04%, 0.06% and 0.08%) for 3, 6, 9, 12 hours treatment periods. Germination parameters like seed germination percentage, seedling height and root length were studied. All three parameter revealed gradual decrease from lower doses to higher doses in given treatments of fungicides benlate.